Adherence to a “MediterrAsian” diet is associated with weight loss-independent improvements in liver fat and lipid profile, but not glucoregulation or inflammation: secondary analysis of a randomized controlled trial - Chooi, Yu Chung; Magkos, Faidon; Yaligar, Jadegoud; Michael, Navin; Sadananthan, Suresh Anand; Kway, Yeshe Manuel; Velan, S. Sendhil; Lim, Kevin Junliang; Lai, Xianning; Wong, Long Hui; Chong, Yap Seng; Loo, Evelyn Xiu Ling; et al. (Frontiers in Nutrition, 2025)
BackgroundGreater adherence to the Mediterranean Diet (MedDiet) has been associated with improved inflammatory biomarkers in Western populations, suggesting that the anti-inflammatory effect is crucial for improvements in body weight, body composition, and cardiometabolic risk factors observed with the MedDiet. We previously reported that a calorie-restricted MedDiet adapted to the Asian food culture has beneficial effects on body composition, liver fat, and cardiometabolic risk markers in Chinese women with fatty liver disease.ObjectiveTo evaluate the effects of MedDiet on inflammation and examine the relationship between dietary adherence and changes in health outcomes.Methods88 non-diabetic Chinese women with fatty liver who participated in a 3-arm, 12-week dietary randomized controlled trial were included in this secondary analysis. Adherence to the MedDiet was assessed using a validated questionnaire. Correlation analysis was performed to identify the relationships between changes in total and food group-specific MedDiet scores and changes in anthropometric measures, body fat percentage, liver fat, muscle and abdominal fat, as well as cardiometabolic and inflammation markers from baseline to post-intervention. Analyses were conducted both without adjustments and after adjusting for weight change.ResultsBody weight, total body fat, visceral and subcutaneous adipose tissues, and liver fat decreased significantly after the intervention, in tandem with improvements in markers of glucose and lipid metabolism and inflammation. The change in MedDiet scores (total and individual food groups) correlated with changes in liver fat and improvements in lipid profile, but not with changes in measures of glucose regulation and inflammation after adjusting for changes in body weight. Increased intake of vegetables, nuts, fish, legumes and olive oil appears to be the main driver of these associations.ConclusionGreater adherence to the MedDiet among nondiabetic Asian women with fatty liver is associated with greater improvements in hepatic fat and lipid profile, but the association with glucose regulation and inflammation is less pronounced. It thus remains unclear whether resolution of inflammation is the key mechanism for the health benefits of MedDiet.Clinical trial registrationclinicaltrials.gov, identifier [NCT05259475].